PENGARUH SALES GROWTH, LEVERAGE, DAN INTENSITAS ASET TETAP TERHADAP TAX AVOIDANCE - Deaztara, Angkasa; Tjakrawala, F.X. Kurniawan (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research hopes to be able to show the influence and relationship that occurs on sales growth, leverage, and the intensity of fixed assets on tax avoidance during 2015 to 2019 in manufacturing companies listed in the Indonesia Stock Exchange. This survey used a sample of 64 companies which were selected based on techniqueof purposive sampling and the research method was quantitative. The data processed in this research was carried out with a program or software using SPSS (Statistical Program for Social Science) version 26 and analyzed recording to multiple linear regression analysis. Data can be obtained through financial statement on the IDX official website. The result explains that the sales growth and leverage variables have a negative but significant effect while, the asset intensity variable has no significant effect on tax avoidance. The implications and suggestions needed are that an increase in sales growth and leverage is needed for decisions made on activities from tax avoidance.